Crimination of Criminal Activities That Caused The Influence of Liquid Drink That Happened in Indonesia - Sitta Bayti Rahma; Fatma Ulfatun Najicha (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The problem of inequality related to wages for workers in a society that we often encounter must be resolved. So, this study aims to determine the effectiveness of the application of the Labor Law on wages of Small and Medium Enterprises workers in the culinary sector in Batam, as well as to see the obstacles that occur in the implementation of wages of Small and Medium Enterprises workers in the culinary sector of Batam City. This reserach is empirical research that is based on events that have occurred in the field regarding the application of the law through a series of observations, interviews with competent government officials, small and medium enterprises in the culinary sector. This research shows that the wages received by most of the Small and Medium Enterprises workers in the culinary sector in Batam City are not feasible, such as the absence of a work agreement as mandated by the Labor Law. This can occur because the Manpower Law does not explicitly accommodate the interests of Small and Medium Enterprises workers in the culinary sector, then the government's lack of awareness in preparing skilled workers, and the low quality of education of workers.